Hydrodynamic Optimization of a Patrol Vessel: Evaluating Stern Foil Configurations on Resistance and Seakeeping via CFD - Eko Prayetno; Fauza Rikzal Ghani; Anton Hekso Yunianto; Muhd Ridho Baihaque; Deny Nusyirwan (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
The operational efficiency and safety of patrol vessels critically depend on minimizing hydrodynamic resistance and enhancing seakeeping performance. This study explores the effect of stern foils with different NACA airfoil sections on a patrol vessel. Employing Computational Fluid Dynamics (CFD), we assessed water resistance in calm conditions and seakeeping traits in regular head seas. Based on the results obtained, the total resistance value (RT) without stern foil shows a value of 202,112 N. Findings show that stern foils lead to a considerable reduction in total resistance, with the NACA 2412 profile achieving the greatest reduction at 14.85%, followed by NACA 64-212 (14.70%) and NACA 4412 (11.67%) at 20 knots and Fn 0.418. Additionally, seakeeping assessments revealed a significant mitigation of pitch and heave motions across all foil designs, notably a marked decrease in pitch Response Amplitude Operator (RAO) at the dominant frequency of 0.13 Hz. This work provides significant contributions to the optimization of patrol vessel design through advanced hydrodynamic additions, contributing to better fuel economy and greater operational stability in challenging maritime environments.